Kebahagiaan Pada Lanjut Usia Ditinjau Dari Keterlibatan Dalam Aktivitas Sehari-Hari - Pertiwi, Rizkya Angkin, Setia Asyanti S.Psi, M.Si (2017)
Happiness is a condition to achieve the needs of the individual who is able to raises positive feelings in themself. Happiness is subjective in nature, though it will continue to looking for happiness as long as individuals are still alive including individuals who have entered the final phase of his life on is an elderly. Not denying the facts show that each year the elderly in Indonesia increasingly experiencing added. From 2000 to 2010 the number of elderly growing as many as 4 million people. It showed that age of elderly life expectancy the higher meaning problems that occur on the elderly is also growing. Problems that occur in the elderly, among others, often dreamy, lamenting her life even up to depression. This can occur because of a person who has entered a period of elderly decline cognitive function, physical and psychic as well as not being able to fulfill its development. To that end, engage in activities of daily living can provide a positive impact for the elderly so that happiness can still be felt by the elderly. The purpose of this research is to know the happiness of the elderly in terms of involvement in activities of daily living. The hypothesis put forward is there is a positive relationship between happiness of the elderly after the terms of engagement in activities of daily living. The research method used was quantitative. The subject of this study using 100 elderly people who incorporated in Ikatan Purnakaryawan Pendidikan dan Kebudayaan (IPPK) Ranting Kecamatan Karangmalang Kabupaten Sragen.. Method of data collection using the scale of activities of daily living and the scale of happiness. While the methods of data retrieval using convenience sampling. The results of a test of normality of activities of daily living variables obtain a Kolmogorov-Smirnov Z = 1,535, with the significance = 0,018 (p < 0,05), so that it can be concluded that the spread of data is abnormal, than the results of a test normality of happiness variables obtain Kolmogorov-Smirnov Z = 1,269 with the significance = 0,080 (p>0,05), so it can be concluded that the spread of data is normal . Based on linear test retrieved the value of F at Deviation from Linierity = 1,489 and significance (p) = 0,087; (p > 0,05). Based on the results of the calculation with the product moment of Spearman correlation coefficient value obtained (rxy) of 0,605; significance (p) = 0.000 (p < 0.01), it means there is a very significant positive relationship between happiness on the elderly with involvement in activities of daily living. Effective contribution between the involvement in activities of daily living variables of happiness on the elderly amounted to 36.6%. From the results of the study also noted that involvement in activities of daily living and happiness on the elderly belongs to high. In addition to come by anyway that most elderly are still working after retirement and also the whole subject is still actively organize and half of it still have a position in the organization and in the community.